The harmonic reduction techniques in shunt active power filter when integrated with non-conventional energy sources - Rao, Kambhampati Venkata Govardhan; Kumar, Malligunta Kiran (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The article covers the control techniques of shunt active filters using switching devices using artificial neural network (ANN) Theory. The basic idea is to achieve perfect disturbance minimization in both steady and transient states. The paper talks about a four-legged converter with a voltage source that can adjust for biased currents and harmonic elements caused by non-linear loads. A shunt connected active filter is used to minimise harmonic currents. The new proposed ANN controller for the improvement of percent total harmonic distortion (THD) is in comparison. The entire power filter concept is based on a MATLAB-modeled with ANN controller. The proposed circuit in this research is studied under various operating situations and simulated, demonstrating the system's potential.